Relocation of the Rich: Migration in Response to Top Tax Rate Changes from Spanish Reforms - Agrawal, David R.; Foremny, Dirk (The Review of Economics and Statistics, 2019)
A Spanish reform granted regions the authority to set income tax rates, resulting in substantial tax differentials. Using administrative data, we find that conditional on moving, taxes have a significant effect on location choice. A 1% increase in the net-of-tax rate for a region relative to others increases the probability of moving to that region by 1.7 percentage points. We estimate an elasticity of the number of top taxpayers with respect to net-of-tax rates of 0.85. The mechanical increase in tax revenue due to higher tax rates is larger than the loss in tax revenue from the net outflow of migration.